The role of student self-government in universities in shaping managerial potential: a study of the development of leadership and organizational skills in Kazakhstan - Shalabayev, Sapar; Xembayeva, Saule; Antikeyeva, Samal; Kudarova, Nazgul; Kayumova, Maya (Frontiers in Education, 2025)
This study investigates the role of student self-government in developing managerial potential among university students in Kazakhstan through a quasi-experimental design. The research assessed how structured participation in self-government affects leadership qualities, organizational skills, and self-efficacy. Two comparable student cohorts were observed over one academic year: an experimental group (n = 90) that participated in a structured self-government program and a control group (n = 78) that followed the standard curriculum. Both groups completed identical pre- and post-intervention assessments using validated psychometric instruments measuring motivation, self-esteem, achievement drive, and psycho-emotional wellbeing. Statistical analyses revealed that the experimental group showed significant improvements in self-orientation, self-esteem, and psycho-emotional indicators (Cohen's d ≈ 0.4–0.6), whereas the control group exhibited no meaningful change. These results demonstrate that systematic engagement in student self-government can moderately enhance managerial potential through experiential leadership practice. The findings underscore the educational value of structured self-governance initiatives for fostering managerial and leadership competencies in higher education.